Low Anterior Resection Syndrome Evaluation and Management - Linhares, Samantha M.; Mongiu, Anne K. (Clinics in Colon and Rectal Surgery, 2025)
Low anterior resection syndrome (LARS) is a constellation of symptoms consisting of stool or flatus incontinence, urgency, and/or clustering of bowel movements. Up to 80% of patients experience these symptoms after sphincter-sparing surgery for rectal cancer with concomitant decrease in quality of life. Multiple measurement tools have been developed and different treatment options have been explored. The purpose of this review was to evaluate LARS assessment tools, treatment options, and the supporting evidence for these strategies. We performed a literature review related to the evaluation and treatment of LARS, and ongoing clinical trials up to 2024 were reviewed. We found the definition of LARS was recently revised, with current validated diagnostic tools lagging behind this update. First-line treatment includes optimizing bowel habits, dietary changes, and medications. Second-line treatment includes pelvic floor rehabilitation or transanal irrigation. Third-line treatment includes sacral nerve stimulation or posterior tibial nerve stimulation before the discussion of antegrade enemas or permanent stoma creation. In summary, LARS remains a challenging symptomatic disorder to capture and treat effectively. There are opportunities for better standardization of preoperative education, evaluation, and escalation of treatment strategies. Further investigation into psychosocial and patient support adjuncts need to be developed. Continued research will help to refine and develop a clear treatment algorithm.
Keywords: rectal cancer; low anterior resection; low anterior resection syndrome